Redescription and molecular diagnosis of Hepatozoon theileri (Laveran, 1905) (Apicomplexa: Adeleorina: Hepatozoidae), infecting Amietia quecketti (Anura: Pyxicephalidae) - Netherlands, Edward C; Cook, Courtney A; Smit, Nico J; du Preez, Louis H (Folia parasitologica, 2014)
Blood smears prepared from the peripheral blood of 20 wild caught Amietia quecketti (Boulenger) from the North-West University Botanical Gardens, North West Province, South Africa, were examined for the presence of haemogregarines. A haemogregarine species comparative in morphology, host and geographical locality to that of Haemogregarina theileri Laveran, 1905 was detected. The original description of H. theileri was based solely on frog peripheral blood gamont stages. Later, further parasite stages, including trophozoites and merogonic liver stages, were recorded in a related Amietia sp. from equatorial Africa. This species was originally classified as a member of the genus Haemogregarina Danilewsky, 1885, but due to the close life cycle and morphological resemblance to those of Hepatozoon species, H. theileri was later transferred from Haemogregarina to Hepatozoon Miller, 1908. In the present study, meront and merozoite stages not described before, along with previously observed trophozoite, immature and mature gamont stages, are described from the peripheral blood of hosts. In addition, comparative phylogenetic analysis of the partial 18S rDNA sequence of Hepatozoon theileri to those of other haemogregarine species, including those of species of Hepatozoon and a Haemogregarina, support the taxonomic transfer of H. theileri to Hepatozoon, nesting H. theileri within a clade comprising species parasitising other amphibians. This is the first molecular and phylogenetic analysis of an African anuran species of Hepatozoon.
Keywords: Apicomplexa; DNA, Ribosomal; protozoální DNA; Ranidae; Animals; parazitární nemoci u zvířat; Phylogeny; fylogeneze; DNA, Protozoan; zvířata; ribozomální DNA; druhová specificita; Parasitic Diseases, Animal; Species Specificity